Orientation and Training Course for Project Executive Officers at Nilokheri - Planning Commission (Planning Commission, 1952)
This document contains lectures delivered at the “Orientation and Training Course for the Project Executive Officers” held in Nilokheri, district Karnal, from July 21, to August 16, 1952. the instructional work at the centre was organised by the Community Projects Administration with the assistance of officers from the Planning Commission, Ministries of Government of India, the State Governments, staff of the T.C.A. and the Ford Foundation, in addition to a number of non-officials, including members of Parliament. In addition to attending the lectures, the Project Executive Officers of the State Governments took part in regular field work in the villages of the Development Block around Nilokheri. Visits to selected projects were also made namely the Etawah project in U.P., Bhadson project in PEPSU, as also the Jumna Canal headworks at Tajewala in the Punjab for purposes of studying what has already been accomplished elsewhere and how it has been done. the lectures are presented here as they were delivered except in some cases where only a summary has been recorded. No attempt has been made to reconcile differences of opinion or points of view expressed by the lecturers. Each lecturer is responsible for the material appearing under his name, which represents his own personal opinion, and should not be taken as representing the policy or views of the C.P.A. the lectures have been arranged according to their subject and have not been presented in the order in which they were delivered. Only significant parts of the discussions that took place after the lectures have been included.
Summary Record of Talks
Government of India